PEMBERDAYAAN USAHA MIKRO KECIL MENENGAH (UMKM) OLEH PERTAMINA MELALUI PROGAM BINAAN UMKM RUMAH BUMN KOTA PEKANBARU TAHUN 2024 - Agustria, Rhemmo Bimola; Rafi, M. (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
According to Law Number 20 of 2008, Micro, Small, and Medium Enterprises (MSMEs) are defined as independent productive economic businesses. In Pekanbaru City, MSME empowerment is facilitated through Rumah BUMN as a platform to support business upgrading. However, many MSMEs still face limited access to capital, weak financial management capacity, lack of business legality, and low utilization of digital media. This study aims to analyze the role of Rumah BUMN in empowering MSMEs in Pekanbaru City. This research employed a qualitative method with a descriptive approach. Data were collected through interviews and documentation, and analyzed using interactive qualitative analysis. The study applies Suharto’s (2021) empowerment principles, namely enabling, strengthening, protecting, supporting, and maintaining. The findings indicate that enabling is achieved through facilitation of access to capital, business legality, training, and participation in local to national exhibitions. Strengthening is implemented through technical, managerial, and digital marketing training that improves business capacity and confidence, although participation remains uneven. Protection is provided through legal assistance, halal certification, BPOM licensing, and BPJS Employment. Support includes mentoring, shared facilities, and financing access.